Clinical characteristics, molecular genetics analysis results and long-term follow-up of a large cohort of congenital hyperinsulinism from Turkey: A nationwide cross-sectional study - Demirbilek, Huseyin; Ozbek, M. Nuri; Yildiz, Melek; Houghton, Jayne L. A.; Onal, Hasan; Gurbuz, Fatih; Flanagan, Sarah E. (Karger, 2023)
[Abstract Not Available]